A Novel Electromagnetic-Neurobiologic Interface for Functional Animation of Dormant Motor Nerve Roots in Spinal Cord Injury via Neuromodulation - Shah, Jawad; Smith, Richard H.; Al-Gharaibeh, Abeer (Frontiers in Surgery, 2020)
Complete spinal cord injury is a devastating occurrence afflicting millions of people worldwide with no available treatment for functional motor recovery. In this report, we describe a procedure in which we used parts of a device available for chronic pain treatment to provide a neuromodulation of motor nerve roots in a case with complete motor and sensory paraplegia. By using a retrograde intra-foraminal approach to implant electrodes close to L2-S1 motor nerve roots bilaterally, we were able to stimulate those nerves and induce precise movements at the joints of lower extremity in a T5 complete spinal cord injury case. We believe that our approach shows potential of the device as a rehabilitation system with the possibility of a parallel electric circuitry that can bridge a damaged spinal cord.